Effects of interactions with the surface on the orientation of the mesogenic monoazacrown-substituted phthalocyanine films - Basova, Tamara; Latteyer, Florian; Atilla, Devrim; Guerek, Ayse Guel; Hassan, Aseel; Ahsen, Vefa; Peisert, Heiko (Elsevier Science Sa, 2010)
In this paper, the effect of interaction with the substrate surface on the orientation of films' molecules of substituted liquid crystalline phthalocyanines M(II)Pc (M = Cu, Ni, Zn) having monoazacrown ether moieties on the periphery containing long alkyloxyphenyl N-pivotal groups is studied. The phthalocyanine derivatives demonstrate thermotropic mesophase behaviour and show Col(h) mesophases over a wide temperature range. The preferential orientation of the phthalocyanine films deposited on glass, silicon and NaCl substrates as well as between two of those substrates is studied by polarized Raman spectroscopy at different temperatures. These phthalocyanines form homeotropically aligned films on the surface of NaCl substrate, whereas planar alignment with a random distribution of the column directors occurs on the glass slides. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Liquid crystal; Thin film; Azacrown ether; Raman spectroscopy